Flow diversion for the treatment of MCA bifurcation aneurysms: a single centre experience - Bhogal, Pervinder; Bäzner, Hansjörg (Frontiers in neurology, 2017)
Background: Intracranial aneurysms located at the bifurcation of the middle cerebral artery (MCA) can often be challenging for the neurointerventionalist. We aimed to evaluate the efficacy and safety of flow diverting stents (FDS) in the treatment of these aneurysms. Material and methods: We retrospectively reviewed our prospectively maintained database to collect information for all patients with unruptured saccular bifurcation MCA aneurysms treated with FDS between January 2010 and January 2016. In additional to demographic data we recorded the location, aneurysm characteristics, previous treatments, number and type of FDS, complications and clinical and angiographic follow-up. Results: Our search identified 13 patients (7 male) with an average age of 61.7 years (47-74yrs). All patients had a single bifurcation aneurysm of the MCA and none of the aneurysms were acutely ruptured. The average fundus size of the saccular aneurysms was 3 mm (range 1.5-10 mm). Follow up studies were available for 12 patients. Based on the most recent follow-up angiograms, 6 aneurysms (50%) were totally occluded; 5 aneurysms (41.7%) showed only a small remnant and 1 aneurysm (8.3 %) remained unchanged. One patient suffered from ischemic stroke with resultant permanent hemiparesis (mRS 3). In another case there was an in-stent thrombosis during the intervention, which resolved upon intra-arterial infusion of Eptifibatide (mRS 0). There were no intra-operative vessel or aneurysm ruptures and no mortalities. Angiography of the covered MCA branches showed no change in the caliber or flow of the vessel in 6 (50%), a reduction in caliber in 5 (41.7%) and a complete occlusion in 1 (8.3%). All caliber changes and occlusions of the vessels were asymptomatic. Conclusions: In our series 91.7% of treated MCA bifurcation aneurysms were either completely occluded or showed only a small remnant with a good safety profile. Flow diversion of MCA bifurcation aneurysms should be considered as an alternative treatment strategy when microsurgical clipping or alternative endovascular treatment options are not feasible.
Gesehen am 20.09.2018